METHODS OF MILITARY-PATRIOTIC EDUCATION OF PUPILS IN GENERAL SECONDARY EDUCATION INSTITUTIONS - Skirda, Tetiana (Theoretical and Methodical Problems of Children and Youth Education, 2024)
The article updates the importance of military-patriotic education of schoolchildren in the context of challenges faced by Ukrainian society in the conditions of military aggression by the Russian Federation against Ukraine. It is substantiated that the military-patriotic upbringing of children and student youth in the education system requires the introduction of modern methodological tools, which include the ideas of statehood, sovereignty and independence of Ukraine, readiness for its protection, awareness of one’s responsibility and involvement in the fate of the state, formation of defence consciousness. The purpose of the article is the analysis and presentation of modern forms and methods of military-patriotic education of students in institutions of general secondary education, which is detailed in the tasks: actualization of the implementation of modern methodological tools of military-patriotic education of student youth in educational institutions; systematization of methods (formation of personal consciousness; formation of experience of social behavior and activity; stimulation of behavior and activity) of military-patriotic education and corresponding forms of work; determining the advantages of using modern methods of military-patriotic education in the formation of the Ukrainian national and civic identity of schoolchildren; determination of the most effective and efficient methods, forms and methods of military-patriotic education based on the analysis of the answers of students of grades 5-11 according to the results of the survey. The research employed the following methods: theoretical (analysis of regulatory frameworks on military-patriotic education, scientific sources, etc.), and statistical (quantitative and qualitative data analysis, data systematization). It has been substantiated that military-patriotic education for children and young students within the educational system requires implementing modern methodological tools. These tools should embody the principles of statehood, sovereignty, and independence of Ukraine, readiness to defend it, awareness of personal responsibility and involvement in the nation's fate, and the formation of a defense-oriented mindset. It was determined that the most effective forms and methods of military-patriotic education for students are trainings, simulation classes, modeling situations, round tables, conversations, discussions, discussion clubs, debates, volunteer initiatives, projects, start-ups, actions, strategic role-playing games, historical quests, motivational talks, lectures, meetings, military sports games, competitions, tournaments, relays, contests, military sports camps, meetings, training.